2011
DOI: 10.1177/1090820x11422700
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Complications With Aptos Sutures

Abstract: Threadlifting is a relatively modern trend in aesthetic surgery that demands a similarly novel approach from surgeons. When performed properly, threadlifting is associated with minor and infrequent complications and is a helpful clinical alternative to traditional facial rejuvenation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 5 publications
2
44
0
Order By: Relevance
“…The adverse effects that we encountered were similar to those reported elsewhere in the literature [6,9,12]. Most complications were self-limited and did not require any intervention.…”
Section: Discussionsupporting
confidence: 86%
“…The adverse effects that we encountered were similar to those reported elsewhere in the literature [6,9,12]. Most complications were self-limited and did not require any intervention.…”
Section: Discussionsupporting
confidence: 86%
“…The thread lift alone was employed in 42 of the 144 patients (29.2%), whereas additional procedures were performed simultaneously in the remaining 102 patients (70.8%). Pain, numbness, discomfort and mild bleeding were excluded in this report, as most patients suffered them and these were transient conditions and recovered by itself within one month [1]. Dimple, thread exposure, alopecia, undercorrection, asymmetry and parotid gland injury were considered here as major complications, as these were longterm impact that required additional procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Thread lifting has been known as a minimally invasive procedure with limited scarring, rapid recovery, and minimal complications compared with the standard incisional surgery for facial rejuvenation [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the following advantages of thread lifts, patient's satisfaction is increasing and their preference is gradually increasing; Short recovery time, good result of face lifting, less pain and minimal scarring. 1 Several kinds of thread in cluding absorbable and non-absorbable have been developed and many studies are reported with effects and complications of thread lift. According to a report by Wu et al, 7 patients experienced post-procedural side effects, including palpable threads with pain, thread migration, infections and granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, thread-lifting is as a minimally invasive technique for facial rejuvenation with minimized scaring and pain. 1,2 It also has less complications compared with standard incisional surgery. 3 Materials for thread-lift may be classified as absorbable or non-absorbable.…”
Section: Introductionmentioning
confidence: 99%